2023
DOI: 10.61650/alj.v1i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Development of Aqidah Akhlak Learning Media "Board Game Based on Education Fun on the Theme of Commendable Morals (E-Fun A2M)" for High School Students

Mochamad Desta Pradana,
Yusuf Olawale Owa-Onire Uthman

Abstract: Monotonous learning patterns lead to ineffective learning behavior which impacts on learning outcomes. Lack of teacher creativity and mastery in processing learning will make students reluctant to take part in learning. The use of learning media as a support for learning is not optimal. The purpose of this study was to develop Board Game Learning Media based on Commendable Morals Education Fun (E-Fun A2M) in Akidah Akhlak High School subjects. This research is research development or Research and Development (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…Oleh karena itu, pendidik harus mengubah pola pikir tersebut agar peserta didik dapat memahami konsep matematika dengan lebih baik menggunakan pendekatan yang kreatif (Arif et al, 2023;Nasiha et al, 2023). Salah satu upaya yang dapat dilakukan adalah dengan mengembangkan komik matematika Islam sebagai alat bantu dalam pembelajaran (Pradana & Uthman, 2023;Rahman, 2023;Winson et al, 2023).…”
Section: Pendahuluanunclassified
“…Oleh karena itu, pendidik harus mengubah pola pikir tersebut agar peserta didik dapat memahami konsep matematika dengan lebih baik menggunakan pendekatan yang kreatif (Arif et al, 2023;Nasiha et al, 2023). Salah satu upaya yang dapat dilakukan adalah dengan mengembangkan komik matematika Islam sebagai alat bantu dalam pembelajaran (Pradana & Uthman, 2023;Rahman, 2023;Winson et al, 2023).…”
Section: Pendahuluanunclassified
“…Kegiatan pembelajaran yang dilakukan di kelas merupakan hal penting yang harus diperhatikan, sehingga diperlukan model pembelajaran yang dapat mengembangkan kemampuan komunikasi matematis siswa (Ahmed & Kumalasari, 2023;Inganah et al, 2023;Muhammad, Agus Triansyah, et al, 2023;Pradana & Uthman, 2023;Sugianto, 2023;Triansyah et al, 2023). Keterlibatan siswa dalam kegiatan tersebut akan memunculkan sikap keberanian dan keaktifan dalam berkompetisi ketika menyelesaikan masalah matematika (Arif et al, 2023;Darmayanti et al, 2023;Lestari et al, 2023;Mustakim & Ngaliyah, 2023;Nasiha et al, 2023;Segara et al, 2023).…”
Section: Pendahuluanunclassified
“…According to Muhammad, Marchy, et al, (2023), learning outcomes can be observed in the form of changes in student behavior that can be measured through changes in knowledge, attitudes, and skills. This change indicates an improvement and better development than before (Ahmed & Kumalasari, 2023;Darmayanti et al, 2023;Nasiha et al, 2023;Pradana & Uthman, 2023). There are several objectives of learning outcomes as stated by Irawan, (2022) providing information about students' progress in achieving learning goals…”
Section: Introductionmentioning
confidence: 98%